1982
DOI: 10.1159/000460843
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Changes in pH during Storage of Platelet Concentrates at 20-24 °C

Abstract: The magnitude of the pH change during platelet concentrate storage at 20-24 °C in polyvinyl chloride containers is not determined solely by platelet count per cubic millimeter of plasma, since a wide variation in pH was observed with similar platelet concentrations. In modified platelet concentrates having lost through centrifugation 3-15% of total platelets and 61-92% of residual leukocytes, the pH was maintained at substantially higher levels than in the paired control platelet concentrates. Leukocyte levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…Platelets from 4-day-stored concentrates were attacked by phospholipase C to an extent which correlated with the pH of the concentrate at day 4. The pH after storage is determined by the platelet count of the concentrate (Murphy & Gardner, 1975;Slichter & Harker, 1976;Moroff et al, 1982; also confirmed in the present study). Platelets from stored concentrates of final pH 6.5-6.9 suffered a 10-1 5% degradation ofphospholipid.…”
Section: Discussionsupporting
confidence: 86%
“…Platelets from 4-day-stored concentrates were attacked by phospholipase C to an extent which correlated with the pH of the concentrate at day 4. The pH after storage is determined by the platelet count of the concentrate (Murphy & Gardner, 1975;Slichter & Harker, 1976;Moroff et al, 1982; also confirmed in the present study). Platelets from stored concentrates of final pH 6.5-6.9 suffered a 10-1 5% degradation ofphospholipid.…”
Section: Discussionsupporting
confidence: 86%
“…However, sufficient oxygen supply seems to be a key factor in the maintenance of oxidative phosphorylation necessary for adequate ATP production/levels [16–19]. Previous studies have also reported various plasters and plasticizers permeability to gases [19–21], high PLT counts, carbon dioxide/oxygen levels [18, 22] and mitochondrial dysfunction [23, 24] as factors important for the maintenance of PLT quality during storage. These results illustrate the complexity of the underlying mechanisms leading to reduced PLT viability.…”
Section: Introductionmentioning
confidence: 99%
“…PLT preparation and storage processes induce the shedding of microparticles that promote thrombosis [4]. During storage, increased glycolysis and reduced mitochondrial function result in glucose depletion, lactic acid accumulation and a fall in pH [5]. The greater the lactic acid production and pH decline, the lower the PLT life span and recovery in the human organism [6].…”
Section: Platelets Stored At Room Temperaturementioning
confidence: 99%